2019
DOI: 10.1080/02673843.2019.1608272
|View full text |Cite
|
Sign up to set email alerts
|

From surviving to thriving: characterizing positive youth development among youth in Ethiopia

Abstract: Studies that characterize youth from a strengths-based perspective are lacking in Africa and specifically in Ethiopia. This study examined the positive development of youth in Ethiopia focusing on their assets profile and corresponding thriving outcomes. Six hundred and thirty-six students (349 girls, 287 boys; Mage = 17.00 years, SD = 1.53; with age range of 13-21 years) drawn from secondary and college preparatory schools in Addis Ababa completed measures on developmental assets and thriving outcomes. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Since the 1990s, the study of adolescence has built up the concepts, tools, and knowledge that have shifted our conception about adolescents away from an expectation of inherent problems, danger and dysfunction to a refocusing on the whole person, which demands a vigorous investigation into the positive potentials of youth collectively as a generation and as diverse individuals on their own terms . The chapters in this book are at the forefront of the contemporary study of adolescence, which is more holistic and contextualized than in the past (e.g., Desie, 2020;. This book provides novel and valuable insights into the specific instances in which young people not only just survive and adapt but also thrive.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, the study of adolescence has built up the concepts, tools, and knowledge that have shifted our conception about adolescents away from an expectation of inherent problems, danger and dysfunction to a refocusing on the whole person, which demands a vigorous investigation into the positive potentials of youth collectively as a generation and as diverse individuals on their own terms . The chapters in this book are at the forefront of the contemporary study of adolescence, which is more holistic and contextualized than in the past (e.g., Desie, 2020;. This book provides novel and valuable insights into the specific instances in which young people not only just survive and adapt but also thrive.…”
Section: Discussionmentioning
confidence: 99%
“…Communitybased youths' photographs of cooperation in securing housing and food and persistence in studying despite inadequate settings (i.e., lack of electricity) express their vision of personal and social resources. In contrast, Ethiopian youth, living in a nearby nation, reported high internal assets, but vulnerable external assets, such as community and school support (Desie, 2019). Higher scores on the measure of ethnic identity (MEIM) suggest that the Maasai maintain a robust tribal and cultural distinctness.…”
Section: Developmental Assets and Cultural Identitymentioning
confidence: 96%
“…In two schools in Lagos, Nigeria, Malik et al [66] found that youth who were peer mentored improved their academic performance more than youth who were exposed to only conventional methods. The environment of Ethiopia is depicted as an asset-depleted society where youth reported less opportunity to engage in activities due to the poor developmental context [67].…”
Section: Empirical Evidence Of Pyd In African Contextsmentioning
confidence: 99%